Impact Smart Applications To Enhance The Transparency and Accuracy Of Financial Auditing - Saddam Catea Hashim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research aimed to analyze the impact of employing artificial intelligence and blockchain technologies in enhancing transparency and accuracy in financial audits.WeeThe research sought to understand how these technologies contribute to improving...ActivitiesAuditing by reducing human errors and enhancing confidence in financial statements.throughData was collected usingQuestionnaire from the research sample, and analysisResults through the statistical programSPSS v 26 and AMOS v 26,The most important conclusions of the research were that applicationsSmart provides the ability to quickly analyze large amounts of financial data, which improves the quality of auditing and decision-makingFinance. WowMRecommendations are a necessityStrengthening cooperation between regulatory authorities and banks to ensure the application of international auditing standards in light of the use of modern technology,The research contributes toAnalysis of the role of intelligent applicationsOhIn improving the accuracy and transparency of financial auditing using advanced technologies.whatHussein audits and detection of financial errorsWhich enhancesConfidence in financial reports by reducing errors and increasing accuracy using smart technology.